Cessation of alcohol consumption decreases rate of nicotine metabolism in male alcohol-dependent smokers. (1st June 2016) - Gubner, Noah R.; Kozar-Konieczna, Aleksandra; Szoltysek-Boldys, Izabela; Slodczyk-Mankowska, Ewa; Goniewicz, Jerzy; Sobczak, Andrzej; Jacob, Peyton; Benowitz, Neal L.; Goniewicz, Maciej L.
Highlights: Nicotine metabolism was examined in alcoholics over 7 weeks of alcohol treatment. Rate of nicotine metabolism was assessed using the nicotine metabolite ratio (NMR). NMR was significantly higher at week 1 compared to week 7 after alcohol cessation. Suggests that chronic alcohol abuse increased the rate of nicotine metabolism. Accelerated rate of nicotine metabolism decreased 4–7 weeks after alcohol cessation in alcoholics. Abstract: Background: Rate of nicotine metabolism is an important factor influencing cigarette smoking behavior, dependence, and efficacy of nicotine replacement therapy. The current study examined the hypothesis that chronic alcohol abuse can accelerate the rate of nicotine metabolism. Nicotine metabolite ratio (NMR, a biomarker for rate of nicotine metabolism) and patterns of nicotine metabolites were assessed at three time points after alcohol cessation. Methods: Participants were 22 Caucasian men randomly selected from a sample of 165 smokers entering a 7-week alcohol dependence treatment program in Poland. Data were collected at three time points: baseline (week 1, after acute alcohol detoxification), week 4, and week 7. Urine was analyzed for nicotine and metabolites and used to determine the nicotine metabolite ratio (NMR, a biomarker for rate of nicotine metabolism), and total nicotine equivalents (TNE, a biomarker for total daily nicotine exposure). Results and conclusions: There was a significant decrease in urine NMR over the 7 weeks after alcohol abstinence (F(2, 42) = 18.83, p < 0.001), indicating a decrease in rate of nicotine metabolism. On average NMR decreased 50.0% from baseline to week 7 (9.6 ± 1.3 vs 4.1 ± 0.6). There was no change in urine TNE across the three sessions, indicating no change daily nicotine intake. The results support the idea that chronic alcohol abuse may increase the rate of nicotine metabolism, which then decreases over time after alcohol cessation. This information may help to inform future smoking cessation interventions in this population.